2016
DOI: 10.1016/j.hjc.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of inadvertent left internal mammarian artery to great cardiac vein fistula

Abstract: Inadvertent left internal mammarian artery to coronary sinus anastomosis is a rare complication of coronary artery by-pass graft surgery. Management of this iatrogenic complication is controversial with conservative, surgical and endovascular options possible. Endovascular treatment offers a minimally invasive approach with a wide variety of embolic agents with different success rates. Herein we present a case of an iatrogenic left internal mammarian artery to coronary sinus anastomosis treated by detachable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Interestingly, since 2011 there are five case reports 18‐22 that included coronary computed tomographic angiography (CTA) as part of their assessment. Graidis et al 23 reported an incidence of 0.15% fistula formation between coronary artery and other coronary vasculature and cardiac chambers using MDCT.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, since 2011 there are five case reports 18‐22 that included coronary computed tomographic angiography (CTA) as part of their assessment. Graidis et al 23 reported an incidence of 0.15% fistula formation between coronary artery and other coronary vasculature and cardiac chambers using MDCT.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism was confirmed on repeat PET after coronary intervention, which demonstrated no evidence of myocardial steal from the LIMA-GCV fistula alone. In the absence of pulmonary hypertension, significant left-to-right shunt or high-output cardiac failure, these arterio-venous fistulae can be treated conservatively [6]. As demonstrated in this case, despite possible dramatic angiographic appearance and prolonged duration of existence, these indirect markers do not necessarily predict shunt fraction and/or clinical significance.…”
Section: Case Descriptionmentioning
confidence: 96%
“…As demonstrated in this case, despite possible dramatic angiographic appearance and prolonged duration of existence, these indirect markers do not necessarily predict shunt fraction and/or clinical significance. Repeat bypass grafting, coil embolization, vascular plug occlusion devices or covered stents in the CS have been used in the treatment of hemodynamically significant LIMA-to-GCV fistulae [2,[6][7][8]. Periodic echocardiographic monitoring of right-sided size and hemodynamics for this patient will, in conjunction with symptoms, determine if an indication arises to treat the shunt.…”
mentioning
confidence: 99%
“…Traditional Coronary Artery Bypass Graft (CABG) is currently among of the chief methods in dealing with patients suffering from atherosclerotic coronary heart disease. It is performed under on-pump and cardiac arrest and is associated with severe injury and a generalized inflammation with many undesired consequences postoperatively (Xu et al, 2020;Bas et al, 2016). To minimize these adverse consequences and with the modern advancement in the vessels targeting and beating cardiac procedures, other techniques were developed.…”
Section: Introductionmentioning
confidence: 99%